Communication—Galvanic Deposition of Gold on Silicon from Au(I) Alkaline Fluoride-Free Solutions. Issue 14 (1st January 2016) - Djokić, S. S.; Antić, Ž.; Djokić, N. S.; Thundat, T.
Abstract : Deposition of gold from alkaline fluoride-free solutions containing Au(I) ions onto silicon surfaces has been demonstrated. This deposition takes place at room temperature and does not require the presence of a reducing agent in the solution. The results clearly show that Au(I) ions can be reduced to Au(0) by silicon and, as a consequence, gold metal can be deposited at the surface of the substrate.